Rebellious Black Femininities in the Select Poems of Nikki Giovanni (International Journal of Food and Nutritional Sciences, 2023)
Rebelliousness in Nikki Giovanni’s Poetry attempts to show how Nikki Giovanni has combined private with public concerns, and her development has been toward the exploration of the inner life of one black female - herself - as a paradigm for black women’s aspirations in contemporary America. An individualist who early admired Ayn Rand’s concept of rational self-interest, Giovanni has a unique black identity. Her example of self-actualization embodied in her poetry has been not only influential but also inspirational, especially to black youth. Her impact on African American literature was immediate and electric. Her celebration of blackness and her militancy placed her in the avantgarde of black letters. Hailed as the Princess of Black Poetry, she began touring the United States, lecturing to college audiences, spreading her message of black cultural nationalism, “ego-tripping,” and love.